Pharmacological Actions of Myricetin in the Nervous System: A Comprehensive Review of Preclinical Studies in Animals and Cell Models - Li, Jie; Xiang, Haitao; Huang, Chao; Lu, Jiashu (Frontiers in Pharmacology, 2021)
Myricetin is a natural flavonoid extracted from a variety of plants, such as medicinal herbs, vegetables, berries, and tea leaves. A growing body of evidence has reported that myricetin supplementation display therapeutic activities in a lot of nervous system disorders, such as cerebral ischemia, Alzheimer’s disease, Parkinson’s disease, epilepsy, and glioblastoma. Myricetin supplementation can also protect against pathological changes and behavioral impairment induced by multiple sclerosis and chronic stress. On the basis of these pharmacological actions, myricetin could be developed as a potential drug for the prevention and/or treatment of nervous system disorders. Mechanistic studies have shown that inhibition of oxidative stress, cellular apoptosis, and neuroinflammatory response are common mechanisms for the neuroprotective actions of myricetin. Other mechanisms, including the activation of the nuclear factor E2-related factor 2 (Nrf2), extracellular signal-regulated kinase 1/2 (ERK1/2), protein kinase B (Akt), cyclic adenosine monophosphate-response element binding protein (CREB), and brain-derived neurotrophic factor (BDNF) signaling, inhibition of intracellular Ca2+ increase, inhibition of c-Jun N-terminal kinase (JNK)-p38 activation, and suppression of mutant protein aggregation, may also mediate the neuroprotective effects of myricetin. Furthermore, myricetin treatment has been shown to promote the activation of the inhibitory neurons in the hypothalamic paraventricular nucleus, which subsequently produces anti-epilepsy effects. In this review, we make a comprehensive understanding about the pharmacological effects of myricetin in the nervous system, aiming to push the development of myricetin as a novel drug for the treatment of nervous system disorders.